The Wilson & Co. Terrace and Roof Garden Restaurants and Soda Fountains, Overlooking the Midway and Lake Michigan (American Colortype Company)
The terrace and roof top garden restaurants and soda fountains occupy the second and third floors of the Wilson & Co. Exhibit Building at A Century of Progress, the first floor beign largely devoted to the already famous Certified Bacon Slicing and Packing demonstration. You may enjoy the best of food, deliciously prepared, at moderate prices, while the pleasing vista of the Midway and the Lake lies before you. Tasty snacks are served at the Lobby food stand on the main floor and also at the ten Wilson Food stands located at convenient spots at the Fair.